Islamophobia as a Form of Radicalisation Perspectives on Media, Academia and Socio-political Scapes from Europe and Canada - d'Haenens, Leen; Mekki-Berrada, Abdelwahed (Leuven University Press, 2023)
Foundations and mechanisms of Islamophobia in the WestIslamophobia as a Form of Radicalisation discusses the scope and fragmented boundaries of Islamophobia as a concept and a sociopolitical reality. The fifteen chapters of this collection cover and connect interdisciplinary research, media content analysis, media discourse analysis, ethnographic research, intersectoral advocacy work, and action research conducted in Belgium, Canada, France, Germany, Poland, Portugal, and Spain. Confronted with an Islamophobia that is growing as a symptom of broader societal malaise in the West, a resistance against it is also arising. It is now a question of better understanding the foundations and mechanisms of this metasolidarity and resistance. Islamophobia as a Form of Radicalisation offers recommendations for urgent consideration by Muslim citizens of Canada and Europe, media professionals, civil society and academic stakeholders, policymakers at the municipal, provincial and federal levels.Contributors: Abdelwahed Mekki-Berrada (Laval University), Alexander Van Leuven (KU Leuven), Alfonso Corral (San Jorge University), Alfredo Brant (Catholic University of Portugal), Anna Flora Machado (Catholic University of Portugal), Anabelle Vanier-Clément (SHERPA University Institute), Ann Trappers (Foyer VZW), Ans De Nolf (KU Leuven), Antonio Prieto-Andrés (San Jorge University), Ashley S. Montgomery (Concordia University), Camila Arêas (University of Reunion), Cayetano Fernández (San Jorge University), Cécile Rousseau (McGill University), Colin Robineau (University of Reunion), David De Coninck (KU Leuven), Erkan Toguslu (KU Leuven), Helena Cruz Ventura (University Institute of Lisbon), Jennifer A. Selby (Memorial University of Newfoundland and Labrador), Jihène Hichri (Université du Québec à Montreal), Joanna Sozańska (Warsaw School of Economics), Katarzyna Górak-Sosnowska (Warsaw School of Economics), Leen d'Haenens (KU Leuven), Luis Manuel Hernández Aguilar (European University Viadrina Frankfurt Oder), Rawda Harb (Concordia University), Salam El-Majzoub (McGill University), Sobia Shaheen Shaikh (Memorial University of Newfoundland and Labrador), Stefan Mertens (KU Leuven), Vivek Venkatesh (Concordia University)Ebook available in Open Access.This publication is GPRC-labeled (Guaranteed Peer-Reviewed Content).